A synthesis and review of the geological evidence for palaeotsunamis along the coast of southeast Australia : the evidence, issues and potential ways forward - Switzer, Adam D. (2013)
In recent years the role of extreme events such as tsunamis and storms in shaping coastal evolution and change has been increasingly appreciated. Around the world, tsunami geologists are increasingly recognising the signatures of palaeotsunamis almost everywhere they look and in many cases, base their interpretations on similar evidence for Quaternary tsunamis first identified in Australia. Geological research suggests that the coast of south east Australia and others worldwide may have been impacted by palaeotsunamis many times larger than the catastrophic 2004 Indian Ocean and 2011 Tōhoku events. In Australia, the debate centres on the hypothesis that the coast of south east Australia preserves evidence for repeated, large magnitude Quaternary tsunamis. If independently validated, this hypothesis has profound implications for risk. Despite the potential importance of this hypothesis, no synthesis or comprehensive review of the proposed geological evidence and chronology exists. As a result it is difficult to assess the evidence and to draw conclusions about the nature of the hazard and risk along the coast. This synthesis details the spatial distribution of reported palaeotsunami deposits along the coast of New South Wales, south east Australia and summarises the distribution of different types of sedimentary and erosional evidence. The age range of reported palaeotsunami deposits is identified and mapped before discussing ‘same age’ (chronologically correlated) deposits. These data are then used to draw broad conclusions about the evidence and identify future research questions to aid in the testing of the hypothesis for repeated tsunami inundation. We show that 60 sites are purported to contain evidence of tsunami inundation over 650 km of the south east Australian coast with a spatial concentration south of Sydney. Geomorphic evidence, distinctly different to that used elsewhere in global palaeotsunami studies, is reported at 54 sites, with erosional features described as the most frequent indication of inundation. Proposed tsunami deposits are evident at 44 sites, with the dominant deposit type being imbricated boulder stacks. Radiocarbon dating at 39 of the sites led to a proposition of nine events during the Quaternary, eight of which occurred during the Holocene. Interestingly, 18 sites have no chronological data associated with them. Alternative interpretations are offered at six type field sites purported to contain palaeotsunami evidence. Attention is drawn to the disjunct between historical and geological scales of tsunami inundation in the region in addition to the contrast between the scale of reported palaeotsunamis and the robust evidence of smaller events. A synthesis of research into the nature of the evidence is offered, including critiques of evidence type and mechanisms. A critical review of the chronological data is also presented, in addition to the recalibration and analysis of published radiocarbon data. The paper concludes with an outline of research questions for further work on proposed palaeotsunami sites in Australia as well as a statement about likely risk in south east Australia. It also advocates the need for caution when interpreting evidence for palaeotsunamis elsewhere around the world when those interpretations are based on signatures originally reported in south east Australia.